Persentuhan Filantropi Islam dan Budaya Lokal: (Studi Terhadap Tradisi Pogogutat Suku Mongondow di Sulawesi Utara) - Muhibbuddin Muhibbuddin (Al-Buhuts, 2019)
Pogogutat culture in the Mongondow tribe in North Sulawesi is one of the local wisdoms in Indonesia which is loaded with various meanings. This cultural presence is in contact with community activities whose purpose is to improve the quality of life of the people. Practically, the tradition of pogogutat is carried out simultaneously by the community if there is one person holding a celebration in the form of providing assistance in the form of material, energy and thoughts. Pogogutat culture among the Mongondow people can be understood among others as a form of an identity as a Muslim community that has the character of ta'awun (please help), helping each other in order to spread the symbols of Islam as part of religious advice. This tradition has a close relationship with the concept of Islamic philanthropy in this case can be interpreted as a movement, both carried out by individuals and groups with the aim of improving the quality of life of society through a "culture of giving".